Статини як одна з причин апоптозу клітин - Панчишин, Ю.М. (Медична гідрологія та реабілітація, 2009)
Apoptosis consists of a distinct form of cell death that displays characteristic alterations in cell morphology and cell fate which are different than death due to oncosis or necrosis. Deregulated apoptosis has been implicated in the development a wide variety of human diseases. Excessive apoptotic cell death may cause organ atrophy and organ failure. On the other hand, insufficient elimination of redundant cells may lead to organ and tissue structural remodeling. Statins induce apoptosis in different cell culture systems.